A high-compaction lithium iron phosphate positive electrode material, a preparation method thereof and a lithium ion battery
Patent Information
- Application Number
- CN202611410323.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-13
AI Technical Summary
虽然常规的湿法两步法工艺尽管突破了传统工艺的限制,但每吨成品会带来2000元~3000元的成本提升,这也限制了其产品大面积推广使用
本发明通过第一次烧结降低了碳含量,保证了颗粒的生长和磁性异物可控。
Smart Images

Figure CN122897384A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and in particular to a high-pressure lithium iron phosphate cathode material, its preparation method, and a lithium-ion battery. Background Technology
[0002] Lithium-ion batteries are widely used due to their high energy density, lack of memory effect, and long cycle life. The cathode material of lithium-ion batteries is crucial influencing their performance and application scenarios. Lithium iron phosphate (LFP) with an olivine structure has become a strong competitor in the power battery market due to its high voltage, high capacity density, long cycle life, high safety, and low cost. As consumers place increasingly higher demands on safety, LFP has once again become the preferred choice for automakers.
[0003] The two-step process for lithium iron phosphate cathode materials provides an effective solution for preparing high-compaction products, achieving a balance between compaction and capacity. While the conventional wet two-step process overcomes the limitations of traditional methods, it increases the cost by 2000-3000 yuan per ton of finished product, limiting its widespread adoption. Cost analysis reveals that the main costs stem from sand milling, spraying, and roller kiln sintering. Summary of the Invention
[0004] This invention provides a high-compaction lithium iron phosphate cathode material and its preparation method, as well as a lithium-ion battery, to overcome the shortcomings of the prior art. The method uses pre-doped lithium iron phosphate as raw material and synthesizes it through a two-step process. The first step involves sintering at different temperatures to prepare large and small lithium iron phosphate particles for the first sintering. The second step uses a low-speed mixer to mix the large and small particles, followed by a second sintering process involving carbon source coating and element doping. A rotary kiln is used for the second sintering, utilizing its dynamic sintering characteristics to effectively avoid secondary particle growth, achieving adjustment of morphology without altering particle size distribution. This invention employs a disc mill for secondary dry coating of the carbon source, ensuring the integrity of the large particle carbon layer. The second sintering uses a dynamic sintering rotary kiln, allowing for better control of particle size distribution. The lithium iron phosphate cathode material prepared by this invention exhibits high compaction, excellent electrical performance, and good cycle performance.
[0005] In order to achieve the objectives of this invention, the following technologies are proposed: The first aspect provides a method for preparing a high-pressure lithium iron phosphate cathode material, including the following steps: Step 01: Mix the first pre-doped iron phosphate, the first lithium source, the first carbon source and deionized water, and then grind, spray dry and sinter at high temperature to obtain the first intermediate; Step 02: Mix the second pre-doped iron phosphate, the second lithium source, the second carbon source and deionized water, and then grind, spray dry, sinter at high temperature and pulverize by airflow to obtain the second intermediate; Step 03: Mix the first intermediate from step 01 and the second intermediate from step 02. During the mixing process, introduce a third carbon source and a first dopant, sinter and pulverize to obtain a high-pressure lithium iron phosphate cathode material.
[0006] Furthermore, in step 01, the first pre-doped iron phosphate Fe / P molar ratio is 0.950 to 0.970, and the specific surface area is 6 m². 2 / g to 10m 2 / g; The in-situ doping element is one or more of Ti, V, Mg, and Mn, and the in-situ doping amount is 2000ppm to 4000ppm; The first lithium source may be one or more of lithium carbonate, lithium phosphate, lithium hydroxide, and lithium dihydrogen phosphate, wherein the molar ratio of Li / Fe is 1.01 to 1.02; The first carbon source is one of glucose, sucrose, polyethylene glycol, and citric acid; The amount of the first carbon source added accounts for 0.6 wt% to 1.0 wt% of the total carbon content in the finished lithium iron phosphate product. The total carbon content of lithium iron phosphate includes the first carbon source and the second carbon source.
[0007] Furthermore, the grinding in step 01 is carried out at a temperature of 10°C to 30°C, with a sand particle size D50 of 0.8 μm to 1.2 μm and a solid content of 30 wt% to 50 wt%. The spray drying process controls the inlet temperature to be between 180°C and 240°C, and the outlet temperature to be between 80°C and 140°C. The particle size D50 of the obtained first intermediate was 20 μm to 60 μm, and the free water content was ≤1.5%. The sintering process is carried out under a nitrogen atmosphere, and the temperature is held at 450℃ for 2 to 4 hours, and then at 800℃ to 820℃ for 6 to 8 hours.
[0008] Furthermore, in step 02, the second pre-doped iron phosphate Fe / P molar ratio is 0.980 to 0.990, and the specific surface area is 12-20 m². 2 / g; The in-situ doping element is one of Ti, V, Mn, and Mg, and the in-situ doping amount is 5000ppm to 9000ppm; The second lithium source is one of lithium hydroxide, lithium oxalate, and lithium acetate, and the Li / Fe molar ratio is 1.03 to 1.04; The second carbon source is one or more of glucose, sucrose, polyethylene glycol, and citric acid, and the amount of the second carbon source added is 1.0 wt% to 1.2 wt% of the carbon content in the finished lithium iron phosphate product.
[0009] Furthermore, the grinding in step 02 is carried out at 10°C to 30°C, with a sand particle size D50 of 0.2 μm to 0.4 μm and a solid content of 30 wt% to 50 wt%. The spray drying process controls the inlet temperature to be between 180°C and 240°C, and the outlet temperature to be between 80°C and 140°C. The resulting second intermediate had a particle size D50 of 20 μm to 60 μm and a free water content ≤1.5%. The sintering process is carried out under a nitrogen atmosphere and held at 700℃ to 760℃ for 4 to 6 hours. The particle size D50 of the second intermediate obtained after air jet milling is between 0.4 μm and 0.6 μm.
[0010] Furthermore, the third carbon source in step 03 is a solution prepared from one of glucose, polyethylene glycol, sucrose, and polyvinylpyrrolidone; The third carbon source accounts for 1.2 wt% to 1.4 wt% of the total carbon content of lithium iron phosphate, wherein the total carbon content of lithium iron phosphate includes the first carbon source and the second carbon source; The first dopant is a soluble titanium source selected from titanium oxysulfate, titanium tetrachloride, titanium citrate, titanium gluconate, and titanium lactate, with a doping amount of 1000ppm to 3000ppm.
[0011] Furthermore, in step 03, the mass ratio of the first intermediate to the second intermediate is 6 to 4: 4 to 6; The mixing process takes 40 minutes inside the mixer. The sintering is carried out in a rotary kiln under a nitrogen atmosphere at a temperature of 780°C to 820°C for 3 to 5 hours. The particle size D50 of the lithium iron phosphate cathode material obtained after air jet pulverization is 0.8 μm to 1.2 μm.
[0012] The second aspect provides a lithium iron phosphate cathode material, which is prepared by the method of high-pressure lithium iron phosphate cathode material.
[0013] A third aspect provides a lithium-ion battery containing the lithium iron phosphate cathode material.
[0014] The advantages of the above technical solution are: This invention reduces the carbon content through the first sintering, ensuring the controllability of particle growth and magnetic foreign matter.
[0015] This invention improves the integrity of the carbon layer by secondary coating of the carbon source and enhances the cycling stability of the material by secondary doping.
[0016] The second sintering of this invention adopts a pure dry method, which can significantly reduce the manufacturing cost of the second sintering process.
[0017] The second sintering of this invention adopts dynamic short-time sintering in a rotary kiln, which can well ensure the stability of particle size distribution and particle roundness. Attached Figure Description
[0018] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will now be described in further detail with reference to the accompanying drawings.
[0019] Figure 1 This is a SEM image of the lithium iron phosphate cathode material prepared in Example 1 of the present invention.
[0020] Figure 2 The graph shows the charge-discharge performance of the lithium iron phosphate cathode material prepared in Example 1 of the present invention.
[0021] Figure 3 This is a particle size distribution diagram of the lithium iron phosphate cathode material prepared in Example 1 of the present invention. Detailed Implementation
[0022] Example 1 20000g of Fe / P with a molar ratio of 0.960 and a specific surface area of 8m² 2 / g and in-situ doped 3000ppm pre-doped iron phosphate and 4972.84g lithium carbonate were mixed, and 1260g glucose, 440g polyethylene glycol and 40000g deionized water were added to form a dispersion. The dispersion was transferred to a sand mill and milled at 20℃, controlling the sand milling particle size D50 to be 1.0μm and the solid content to be 40wt%, to obtain a slurry. The slurry was spray dried, controlling the inlet air temperature to be 210℃ and the outlet air temperature to be 110℃, to granulate a precursor powder with a granulation D50 of 40μm and a free water content ≤1.5%. The obtained precursor powder was kept at 450℃ for 3h, and then the temperature was raised to 810℃ and kept at 7h, with nitrogen as the protective atmosphere, to obtain the first intermediate.
[0023] 20000g of Fe / P with a molar ratio of 0.985 and a specific surface area of 16m² 2 / g and in-situ doped 7000ppm pre-doped iron phosphate and 5070.82g lithium carbonate were mixed, and 1560g sucrose, 960g citric acid and 41300g deionized water were added to form a dispersion. The dispersion was transferred to a sand mill and milled at 20℃, controlling the sand milling particle size D50 to be 0.3μm and the solid content to be 40wt%, to obtain a slurry. The slurry was spray dried, controlling the inlet air temperature to be 210℃ and the outlet air temperature to be 110℃, to granulate a precursor powder with a particle size D50 of 40μm and a free water content ≤1.5%. The obtained precursor powder was kept at 730℃ for 5h under a nitrogen protective atmosphere. Then it was pulverized, controlling the particle size D50 to be 0.5μm, to obtain the second intermediate.
[0024] 120g of polyethylene glycol was dispersed in 120g of deionized water and heated to dissolve, resulting in a polyethylene glycol solution. 70.2g of titanium citrate was then added. 2000g of the first intermediate and 2000g of the second intermediate were mixed (mass ratio 1:1) and sprinkled into the prepared solution. The mixing time was 40min. The resulting mixture was sintered in a rotary kiln at 800℃ for 4h under nitrogen atmosphere. The mixture was then pulverized to control the particle size D50 at 1.0μm, resulting in high-pressure lithium iron phosphate material with a carbon content of 1.3wt%.
[0025] Example 2 20000g of Fe / P with a molar ratio of 0.950 and a specific surface area of 6m² 2 / g and in-situ doped 4000ppm pre-doped iron phosphate and 4997.33g lithium carbonate were mixed, and 1060g glucose, 400g polyvinylpyrrolidone and 62000g deionized water were added to form a dispersion. The dispersion was transferred to a sand mill and milled at 10℃, controlling the sand milling particle size D50 to be 0.8μm and the solid content to be 30wt%, to obtain a slurry. The slurry was spray dried, controlling the inlet air temperature to be 240℃ and the outlet air temperature to be 140℃, to granulate a precursor powder with a granulation D50 of 60μm and a free water content ≤1.5%. The obtained precursor powder was kept at 450℃ for 4h, and then the temperature was raised to 800℃ and kept at 6h, with nitrogen as the protective atmosphere, to obtain the first intermediate.
[0026] 20000g of Fe / P with a molar ratio of 0.990 and a specific surface area of 20m² 2 / g and 5000ppm of pre-doped iron phosphate and 5046.33g of lithium carbonate were mixed, and 540g of glucose, 800g of polyvinylpyrrolidone and 61000g of deionized water were added to form a dispersion. The dispersion was transferred to a sand mill and milled at 10℃, controlling the particle size D50 to be 0.2μm and the solid content to be 30wt%, to obtain a slurry. The slurry was spray-dried, controlling the inlet air temperature to be 240℃ and the outlet air temperature to be 140℃, to granulate a precursor powder with a particle size D50 of 60μm and a free water content ≤1.5%. The obtained precursor powder was kept at 760℃ for 4h under a nitrogen atmosphere. Then it was pulverized, controlling the particle size D50 to be 0.6μm, to obtain the second intermediate.
[0027] 84g of glucose was dispersed in 84g of deionized water and heated to dissolve, resulting in a glucose solution. 101.2g of titanium lactate was then added. 2400g of the first intermediate and 1600g of the second intermediate were mixed (mass ratio 2:3) and sprinkled into the prepared solution. The mixing time was 40min. The resulting mixture was sintered in a rotary kiln at 780℃ for 5h under nitrogen atmosphere. The mixture was then pulverized to control the particle size D50 at 1.2μm, resulting in high-pressure lithium iron phosphate material with a carbon content of 1.4wt%.
[0028] Example 3 20000g of Fe / P with a molar ratio of 0.970 and a specific surface area of 10m² 2 / g and 2000ppm of pre-doped iron phosphate and 4948.34g of lithium carbonate were mixed, and 800g of sucrose, 1400g of citric acid and 28000g of deionized water were added to form a dispersion. The dispersion was transferred to a sand mill and milled at 30℃, controlling the particle size D50 to be 1.2μm and the solid content to be 50wt%, to obtain a slurry. The slurry was spray-dried, controlling the inlet air temperature to be 180℃ and the outlet air temperature to be 80℃, to granulate a precursor powder with a D50 of 20μm and a free water content ≤1.5%. The obtained precursor powder was kept at 450℃ for 2h, and then the temperature was raised to 820℃ and kept at 8h, with nitrogen as the protective atmosphere, to obtain the first intermediate.
[0029] 20000g of Fe / P with a molar ratio of 0.980 and a specific surface area of 12m² 2 / g and in-situ doped 9000ppm pre-doped iron phosphate and 5095.32g lithium carbonate were mixed, and 1480g sucrose, 1580g citric acid and 28000g deionized water were added to form a dispersion. The dispersion was transferred to a sand mill and milled at 30℃, controlling the milling particle size D50 to be 0.4μm and the solid content to be 50wt%, to obtain a slurry. The slurry was spray-dried, controlling the inlet air temperature to be 180℃ and the outlet air temperature to be 80℃, to granulate a precursor powder with a particle size D50 of 20μm and a free water content ≤1.5%. The obtained precursor powder was kept at 700℃ for 6h under a nitrogen protective atmosphere. Then it was pulverized, controlling the particle size D50 to be 0.4μm, to obtain the second intermediate.
[0030] 84g of glucose was dispersed in 84g of deionized water and heated to dissolve, resulting in a glucose solution. 13.36g of titanium oxysulfate was then added. 1600g of the first intermediate and 2400g of the second intermediate were mixed (mass ratio 3:2) and sprinkled into the prepared solution. The mixing time was 40min. The resulting mixture was sintered in a rotary kiln at 820℃ for 3h under nitrogen atmosphere. The mixture was then pulverized to control the particle size D50 at 0.8μm, yielding a high-pressure lithium iron phosphate material with a carbon content of 1.2wt%.
[0031] Comparative Example 1 A mixture of 20,000 g of ferric phosphate and 100.1 g of titanium dioxide, along with 4,972.84 g of lithium carbonate, was mixed with 1,260 g of glucose, 440 g of polyethylene glycol, and 40,000 g of deionized water to form a dispersion. The dispersion was then transferred to a sand mill and milled at 20°C, controlling the particle size D50 to be 1.0 μm and the solid content to be 40 wt%, to obtain a slurry. The slurry was then spray-dried, controlling the inlet air temperature to be 210°C and the outlet air temperature to be 110°C, to obtain a precursor powder with a granulation D50 of 40 μm and a free water content ≤1.5%. The obtained precursor powder was then kept at 450°C for 3 h, followed by raising the temperature to 810°C and keeping it there for 7 h, with nitrogen as the protective atmosphere, to obtain the first intermediate.
[0032] A mixture of 20,000 g of ferric phosphate and 233.6 g of titanium dioxide, along with 5,070.82 g of lithium carbonate, was mixed with 1,560 g of sucrose, 960 g of citric acid, and 41,300 g of deionized water to form a dispersion. The dispersion was then milled in a sand mill at 20°C, controlling the particle size D50 to be 0.3 μm and the solid content to be 40 wt%, yielding a slurry. The slurry was then spray-dried, controlling the inlet air temperature to be 210°C and the outlet air temperature to be 110°C, resulting in a precursor powder with a granulation D50 of 40 μm and a free water content ≤1.5%. The obtained precursor powder was then held at 730°C for 5 hours under a nitrogen atmosphere. Finally, it was pulverized, controlling the particle size D50 to be 0.5 μm, to obtain the second intermediate.
[0033] 120g of polyethylene glycol was dispersed in 120g of deionized water and heated to dissolve, resulting in a polyethylene glycol solution. 70.2g of titanium citrate was then added. 2000g of the first intermediate and 2000g of the second intermediate were mixed (mass ratio 1:1) and sprinkled into the prepared solution. The mixing time was 40min. The resulting mixture was sintered in a rotary kiln at 800℃ for 4h under nitrogen atmosphere. The mixture was then pulverized to control the particle size D50 at 1.0μm, resulting in high-pressure lithium iron phosphate material with a carbon content of 1.3wt%.
[0034] Comparative Example 2 20000g of Fe / P with a molar ratio of 0.960 and a specific surface area of 8m² 2 / g and in-situ doped pre-doped iron phosphate (3000ppm) and 4972.84g lithium carbonate were mixed, and 1260g glucose, 740g polyethylene glycol and 40000g deionized water were added to form a dispersion. The dispersion was transferred to a sand mill and milled at 20℃, controlling the particle size D50 to be 1.0μm and the solid content to be 40wt%, to obtain a slurry. The slurry was spray-dried, controlling the inlet air temperature to be 210℃ and the outlet air temperature to be 110℃, to granulate a precursor powder with a granulation D50 of 40μm and a free water content ≤1.5%. The obtained precursor powder was kept at 450℃ for 3h, and then the temperature was raised to 810℃ and kept at 7h, with nitrogen as the protective atmosphere, to obtain the first intermediate.
[0035] 20000g of Fe / P with a molar ratio of 0.985 and a specific surface area of 16m² 2 / g and in-situ doped 7000ppm pre-doped iron phosphate and 5070.82g lithium carbonate were mixed, and 1260g glucose and 740g polyethylene glycol were added to form a dispersion. The dispersion was transferred to a sand mill and sand-milled at 20℃, controlling the sand milling particle size D50 to be 0.3μm and the solid content to be 40wt%, to obtain a slurry. The slurry was spray-dried, controlling the inlet air temperature to be 210℃ and the outlet air temperature to be 110℃, to granulate a precursor powder with a granulation D50 of 40μm and a free water content ≤1.5%. The obtained precursor powder was kept at 730℃ for 5h under a nitrogen protective atmosphere. Then it was pulverized, controlling the particle size D50 to be 0.5μm, to obtain the second intermediate.
[0036] 120g of polyethylene glycol was dispersed in 120g of deionized water and heated to dissolve, resulting in a polyethylene glycol solution. 70.2g of titanium citrate was then added. 2000g of the first intermediate and 2000g of the second intermediate were mixed (mass ratio 1:1) and sprinkled into the prepared solution. The mixing time was 40min. The resulting mixture was sintered in a rotary kiln at 800℃ for 4h under nitrogen atmosphere. The mixture was then pulverized to control the particle size D50 at 1.0μm, resulting in high-pressure lithium iron phosphate material with a carbon content of 1.3wt%.
[0037] Comparative Example 3 20000g of Fe / P with a molar ratio of 0.960 and a specific surface area of 8m² 2 / g and in-situ doped pre-doped iron phosphate (3000ppm) and 4972.84g lithium carbonate were mixed, and 1260g glucose, 740g polyethylene glycol and 40000g deionized water were added to form a dispersion. The dispersion was transferred to a sand mill and milled at 20℃, controlling the particle size D50 to be 1.0μm and the solid content to be 40wt%, to obtain a slurry. The slurry was spray-dried, controlling the inlet air temperature to be 210℃ and the outlet air temperature to be 110℃, to granulate a precursor powder with a granulation D50 of 40μm and a free water content ≤1.5%. The obtained precursor powder was kept at 450℃ for 3h, and then the temperature was raised to 810℃ and kept at 7h, with nitrogen as the protective atmosphere, to obtain the first intermediate.
[0038] 20000g of Fe / P with a molar ratio of 0.985 and a specific surface area of 16m² 2 / g and in-situ doped 7000ppm pre-doped iron phosphate and 5070.82g lithium carbonate were mixed, and 1560g sucrose, 960g citric acid and 41300g deionized water were added to form a dispersion. The dispersion was transferred to a sand mill and milled at 20℃, controlling the sand milling particle size D50 to be 0.3μm and the solid content to be 40wt%, to obtain a slurry. The slurry was spray dried, controlling the inlet air temperature to be 210℃ and the outlet air temperature to be 110℃, to granulate a precursor powder with a particle size D50 of 40μm and a free water content ≤1.5%. The obtained precursor powder was kept at 730℃ for 5h under a nitrogen protective atmosphere. Then it was pulverized, controlling the particle size D50 to be 0.5μm, to obtain the second intermediate.
[0039] 120g of polyethylene glycol was dispersed in 120g of deionized water and heated to dissolve, resulting in a polyethylene glycol solution. 70.2g of titanium citrate was then added. 2000g of the first intermediate and 2000g of the second intermediate were mixed and sprinkled into the prepared solution. The mixing time was 40min. The resulting mixture was sintered in a roller kiln at 800℃ for 4h under nitrogen atmosphere. The mixture was then pulverized to control the particle size D50 at 1.0μm, resulting in high-pressure lithium iron phosphate material with a carbon content of 1.3wt%.
[0040] Comparative Example 4 20000g of Fe / P with a molar ratio of 0.960 and a specific surface area of 8m² 2 / g and in-situ doped 3000ppm pre-doped iron phosphate and 4972.84g lithium carbonate were mixed, and 1260g glucose, 440g polyethylene glycol and 40000g deionized water were added to form a dispersion. The dispersion was transferred to a sand mill and milled at 20℃, controlling the sand milling particle size D50 to be 1.0μm and the solid content to be 40wt%, to obtain a slurry. The slurry was spray dried, controlling the inlet air temperature to be 210℃ and the outlet air temperature to be 110℃, to granulate a precursor powder with a granulation D50 of 40μm and a free water content ≤1.5%. The obtained precursor powder was kept at 450℃ for 3h, and then the temperature was raised to 810℃ and kept at 7h, with nitrogen as the protective atmosphere, to obtain the first intermediate.
[0041] 20000g of Fe / P with a molar ratio of 0.985 and a specific surface area of 16m² 2 / g and in-situ doped 7000ppm pre-doped iron phosphate and 5070.82g lithium carbonate were mixed, and 1560g sucrose, 960g citric acid and 41300g deionized water were added to form a dispersion. The dispersion was transferred to a sand mill and milled at 20℃, controlling the sand milling particle size D50 to be 0.3μm and the solid content to be 40wt%, to obtain a slurry. The slurry was spray dried, controlling the inlet air temperature to be 210℃ and the outlet air temperature to be 110℃, to granulate a precursor powder with a particle size D50 of 40μm and a free water content ≤1.5%. The obtained precursor powder was kept at 730℃ for 5h under a nitrogen protective atmosphere. Then it was pulverized, controlling the particle size D50 to be 0.5μm, to obtain the second intermediate.
[0042] 120g of polyethylene glycol was dispersed in 120g of deionized water and heated to dissolve, resulting in a polyethylene glycol solution. 70.2g of titanium citrate was then added. 8000g of the first intermediate and 2000g of the second intermediate were mixed (mass ratio 4:1) and sprinkled into the prepared solution. The mixing time was 40min. The resulting mixture was sintered in a rotary kiln at 800℃ for 4h under nitrogen atmosphere. The mixture was then pulverized to control the particle size D50 at 1.0μm, resulting in high-pressure lithium iron phosphate material with a carbon content of 1.3wt%.
[0043] Comparative Example 5 20000g of Fe / P with a molar ratio of 0.960 and a specific surface area of 8m² 2 / g and in-situ doped 3000ppm pre-doped iron phosphate and 4972.84g lithium carbonate were mixed, and 1260g glucose, 440g polyethylene glycol and 40000g deionized water were added to form a dispersion. The dispersion was transferred to a sand mill and milled at 20℃, controlling the sand milling particle size D50 to be 1.0μm and the solid content to be 40wt%, to obtain a slurry. The slurry was spray dried, controlling the inlet air temperature to be 210℃ and the outlet air temperature to be 110℃, to granulate a precursor powder with a granulation D50 of 40μm and a free water content ≤1.5%. The obtained precursor powder was kept at 450℃ for 3h, and then the temperature was raised to 810℃ and kept at 7h, with nitrogen as the protective atmosphere, to obtain the first intermediate.
[0044] 20000g of Fe / P with a molar ratio of 0.985 and a specific surface area of 16m² 2 / g and in-situ doped 7000ppm pre-doped iron phosphate and 5070.82g lithium carbonate were mixed, and 1560g sucrose, 960g citric acid and 41300g deionized water were added to form a dispersion. The dispersion was transferred to a sand mill and milled at 20℃, controlling the sand milling particle size D50 to be 0.3μm and the solid content to be 40wt%, to obtain a slurry. The slurry was spray dried, controlling the inlet air temperature to be 210℃ and the outlet air temperature to be 110℃, to granulate a precursor powder with a particle size D50 of 40μm and a free water content ≤1.5%. The obtained precursor powder was kept at 730℃ for 5h under a nitrogen protective atmosphere. Then it was pulverized, controlling the particle size D50 to be 0.5μm, to obtain the second intermediate.
[0045] 120g of polyethylene glycol was dispersed in 120g of deionized water and heated to dissolve, resulting in a polyethylene glycol solution. 70.2g of titanium citrate was then added. 2000g of the first intermediate and 8000g of the second intermediate were mixed (mass ratio 1:4) and sprinkled into the prepared solution. The mixing time was 40min. The resulting mixture was sintered in a rotary kiln at 800℃ for 4h under nitrogen atmosphere. The mixture was then pulverized to control the particle size D50 at 1.0μm, resulting in high-pressure lithium iron phosphate material with a carbon content of 1.3wt%.
[0046] Further tests were conducted on Examples 1-3 and Comparative Examples 1-5. Specifically, the lithium iron phosphate cathode materials prepared in Examples 1-3 and Comparative Examples 1-5 were photographed using a 10kx scanning electron microscope; 1g of the lithium iron phosphate cathode materials prepared in Examples 1-3 and Comparative Examples 1-5 were weighed and placed into a compaction mold, and the mold was placed in a compaction device to start the test. The powder compaction density result was taken as the result under a pressure of 30kN; the lithium iron phosphate cathode materials prepared in Examples 1-3 and Comparative Examples 1-5 were dispersed in NMP with Super-P and PVDF at a mass ratio of 80:10:10, ball-milled to disperse evenly, coated on aluminum foil, and vacuum dried to obtain a cathode sheet. The electrolyte was 1mol / L LiPF6, with a solvent volume ratio of EC:DMC:EMC = 1:1:1 (volume ratio). The separator was a polypropylene membrane, and the lithium metal sheet was used as the negative electrode. They were assembled together to form a coin cell. The test voltage range was 2.0V-3.75V. The voltage was charged to 3.75V using a constant current / constant voltage charging method, and then discharged to 2.0V using a constant current discharging method. The charge / discharge current was 0.1C for 2 cycles; then, a 1C charge / discharge current was used for 2 cycles, with the cutoff voltage condition the same as at 0.1C. The test results are shown in the table below.
[0047] As can be seen from the above results, the lithium iron phosphate cathode material prepared in the embodiments of the present invention has higher powder compaction and better capacity.
[0048] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Obviously, those skilled in the art can make various modifications and variations to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention also intends to include these modifications and variations.
Claims
1. A method for preparing a high-pressure lithium iron phosphate cathode material, characterized in that, Including the following steps: Step 01: Mix the first pre-doped iron phosphate, the first lithium source, the first carbon source and deionized water, and then grind, spray dry and sinter at high temperature to obtain the first intermediate; Step 02: Mix the second pre-doped iron phosphate, the second lithium source, the second carbon source and deionized water, and then grind, spray dry, sinter at high temperature and pulverize by airflow to obtain the second intermediate; Step 03: Mix the first intermediate from step 01 and the second intermediate from step 02. During the mixing process, introduce a third carbon source and a first dopant, sinter and pulverize to obtain a high-pressure lithium iron phosphate cathode material.
2. The method for preparing high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that: In step 01, the first pre-doped iron phosphate (Fe / P) molar ratio is 0.950 to 0.970, and the specific surface area is 6 m². 2 / g to 10m 2 / g; The in-situ doping element is one or more of Ti, V, Mg, and Mn, and the in-situ doping amount is 2000ppm to 4000ppm; The first lithium source may be one or more of lithium carbonate, lithium phosphate, lithium hydroxide, and lithium dihydrogen phosphate, wherein the molar ratio of Li / Fe is 1.01 to 1.02; The first carbon source is one of glucose, sucrose, polyethylene glycol, and citric acid; The amount of the first carbon source added accounts for 0.6 wt% to 1.0 wt% of the total carbon content in the finished lithium iron phosphate product. The total carbon content of lithium iron phosphate includes the first carbon source and the second carbon source.
3. The method for preparing high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that: The grinding in step 01 is carried out at a temperature of 10°C to 30°C, with a sand particle size D50 of 0.8 μm to 1.2 μm and a solid content of 30 wt% to 50 wt%. The spray drying process controls the inlet temperature to be between 180°C and 240°C, and the outlet temperature to be between 80°C and 140°C. The particle size D50 of the obtained first intermediate was 20 μm to 60 μm, and the free water content was ≤1.5%. The sintering process is carried out under a nitrogen atmosphere, and the temperature is held at 450℃ for 2 to 4 hours, and then at 800℃ to 820℃ for 6 to 8 hours.
4. The method for preparing high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that: In step 02, the second pre-doped iron phosphate (Fe / P) molar ratio is 0.980 to 0.990, and the specific surface area is 12-20 m². 2 / g; The in-situ doping element is one of Ti, V, Mn, and Mg, and the in-situ doping amount is 5000ppm to 9000ppm; The second lithium source is one of lithium hydroxide, lithium oxalate, and lithium acetate, and the Li / Fe molar ratio is 1.03 to 1.04; The second carbon source is one or more of glucose, sucrose, polyethylene glycol, and citric acid, and the amount of the second carbon source added is 1.0 wt% to 1.2 wt% of the carbon content in the finished lithium iron phosphate product.
5. The method for preparing high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that: The grinding in step 02 is carried out at 10°C to 30°C, with a sand particle size D50 of 0.2 μm to 0.4 μm and a solid content of 30 wt% to 50 wt%. The spray drying process controls the inlet temperature to be between 180°C and 240°C, and the outlet temperature to be between 80°C and 140°C. The resulting second intermediate had a particle size D50 of 20 μm to 60 μm and a free water content ≤1.5%. The sintering process is carried out under a nitrogen atmosphere and held at 700℃ to 760℃ for 4 to 6 hours. The particle size D50 of the second intermediate obtained after air jet milling is between 0.4 μm and 0.6 μm.
6. The method for preparing high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that, The third carbon source in step 03 is a solution prepared from one of glucose, polyethylene glycol, sucrose, and polyvinylpyrrolidone; The third carbon source accounts for 1.2 wt% to 1.4 wt% of the total carbon content of lithium iron phosphate, wherein the total carbon content of lithium iron phosphate includes the first carbon source and the second carbon source; The first dopant is a soluble titanium source selected from titanium oxysulfate, titanium tetrachloride, titanium citrate, titanium gluconate, and titanium lactate, with a doping amount of 1000ppm to 3000ppm.
7. The method for preparing high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that, In step 03, the mass ratio of the first intermediate to the second intermediate is 6 to 4: 4 to 6. The mixing process takes 40 minutes inside the mixer. The sintering is carried out in a rotary kiln under a nitrogen atmosphere at a temperature of 780°C to 820°C for 3 to 5 hours. The particle size D50 of the lithium iron phosphate cathode material obtained after air jet pulverization is 0.8 μm to 1.2 μm.
8. A lithium iron phosphate cathode material, characterized in that, It is prepared by the method for preparing high-pressure lithium iron phosphate cathode material as described in any one of claims 1 to 7.
9. A lithium-ion battery, characterized in that, The lithium-ion battery contains the lithium iron phosphate cathode material as described in claim 8.